Revolutionized attitude toward recurrent pregnancy loss and recurrent implantation failure based on precision regenerative medicine - Kimia Motlagh Asghari; Tannaz Novinbahador; Amir Mehdizadeh; Mohammadali Zolfaghari; Mehdi Yousefi (Heliyon)
Traditional treatment strategies for recurrent pregnancy loss (RPL) and recurrent implantation failure (RIF) often result in limited success, placing significant emotional and financial burdens on couples. However, novel approaches such as diagnostic gene profiling, cell therapy, stem cell-derived exosome therapy, and pharmacogenomics offer promising, personalized treatments. Combining traditional treatments with precision and regenerative medicine may enhance the efficacy of these approaches and improve pregnancy outcomes. This review explores how integrating these strategies can potentially transform the lives of couples experiencing repeated pregnancy loss or implantation failure, providing hope for improved treatment success. Precision and regenerative medicine represent a new frontier for managing RPL and RIF, offering promising solutions.